2014
DOI: 10.21886/2308-6424-2014-0-4-3-12
|View full text |Cite
|
Sign up to set email alerts
|

Own Experience of Surgical Treatment of Blunt Renal Trauma

Abstract: Проанализирована эффективность оперативного лечения 37 пациентов с закрытой травмой почки, которые находились в клинике с 1989 по 2013 На основе собственного опыта и общепринятых стандартов очерчены особенности диагностики и лечения этой патологии. В практической деятельности использованы классификации, предложенные Американской ассоциацией хирургии травм (ААХТ) в 1989 и профессором С.А. Возиановым и профессором А.В. Шуляком в 2003 Полученные результаты свидетельствуют об эффективности оперативного лечения у п… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
1
0
1
Order By: Relevance
“…Percutaneous nephrolithotomy is more common on the left side, and the lower calyceal puncture is the most frequent puncture site in PCNL, which could explain these findings. More than half of our patients had pseudoaneurysm alone or with other lesions, in agreement with other published series, [7,14,16] where pseudoaneurysm was the most common lesion. A pseudoaneurysm occurs when a blood vessel wall is injured, and extravasating blood collects in the surrounding tissue.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Percutaneous nephrolithotomy is more common on the left side, and the lower calyceal puncture is the most frequent puncture site in PCNL, which could explain these findings. More than half of our patients had pseudoaneurysm alone or with other lesions, in agreement with other published series, [7,14,16] where pseudoaneurysm was the most common lesion. A pseudoaneurysm occurs when a blood vessel wall is injured, and extravasating blood collects in the surrounding tissue.…”
Section: Discussionsupporting
confidence: 93%
“…As reported, there was an overuse of RAE that included many minor renal traumas (grades I–III). Vozianov et al, [ 14 ] in another series that included 20 patients with blunt renal trauma, reported a 90% success rate with RAE on the first attempt and 10% after repeated procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[5,8] Hablando específicamente de la embolización de la arteria renal, en el estudio de Vozianov et al se encontró que un 25% de los pacientes (AAST grado II-IV) presentaron complicaciones pudiendo ser inclusive 2 o más. [19] La complicación más frecuente es el síndrome postembolización en el que el paciente se presenta 1 a 3 días después del procedimiento con un cuadro de dolor en flanco, fiebre, náuseas y vómitos; es un cuadro autolimitado y el tratamiento es de soporte. [16] Otras complicaciones que, aunque raras, pueden ocurrir son: migración del dispositivo espiral endovascular o coil, insuficiencia adrenal, hipertensión transitoria, nefrotoxicidad por contraste, infección con formación de absceso y hematoma del sitio de acceso.…”
Section: Trombosis De Arteria O Vena Renalunclassified